2011
DOI: 10.1590/s1677-55382011000600022
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Gleason pattern 5 on prostatic needle core biopsy: frequency of underdiagnosis and relation to morphology

Abstract: Urological Survey 790 features and a malignant or benign diagnosis. The sensitivity, specificity, and positive and negative predictive values of progressive enhancement for a diagnosis of benignity were 60%, 73%, 43%, and 84%. Conclusion: In the evaluation of enhancing small solid renal lesions without fat, no CT criteria were of substantial help in differentiating malignant from benign lesions. Editorial CommentPre-operative characterization of small solid enhancing renal lesion containing no macroscopic fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 0 publications
3
23
0
1
Order By: Relevance
“…Previous studies have also reported that the GP5 remained underdiagnosed in the clinical practice. 12,14 Fajardo and colleagues examined the frequency of underdiagnoses and its relation to the morphology of GP5 in a consultation practice. They reported that pattern 5 was missed by pathologists more frequently when it represented the secondary or tertiary component of the PCa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also reported that the GP5 remained underdiagnosed in the clinical practice. 12,14 Fajardo and colleagues examined the frequency of underdiagnoses and its relation to the morphology of GP5 in a consultation practice. They reported that pattern 5 was missed by pathologists more frequently when it represented the secondary or tertiary component of the PCa.…”
Section: Discussionmentioning
confidence: 99%
“…13 Several additional patterns, not formally recognized in the 2005 ISUP modification of the Gleason consensus, which included tumor sheets with a vague attempt to luminal formation, single file, solid nested, and solid cylinder patterns, have also been proposed to represent GP5. 14,15 Because of its prognostic and therapeutic significance, accurate recognition of GP5 PCa is critical for patient management. However, 2 important points regarding the pathologic diagnosis of GP5 PCa have not been adequately addressed: (1) the diagnostic reproducibility of different Gleason 5 patterns;and (2) the quantitative threshold for a diagnosis of pattern 5, based on the minimum volume of pattern 5 present.…”
mentioning
confidence: 99%
“…An important feature of the Gleason grading is that it does not rely on detailed assessment of nuclear morphology, but it assigns numerical grades (1)(2)(3)(4)(5) based upon the architectural patterns of the tumour that are best evaluated at low power magnification. Patterns 1, 2 and 3 represent tumours that most closely resemble normal prostate gland, and patterns 4 and 5 are tumours showing increasingly abnormal glandular architecture (Gleason, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…4 Comedo necrosis is distinctly uncommon, being found in only 2% of all Gleason pattern 5 cases in 1 needle biopsy series. 5 These growth arrangements are often admixed, such that it is uncommon to see a pure growth arrangement. 4 With high grade Gleason patterns 4 and 5 there is typically extensive involvement of needle core tissue, with multiple cores involved by carcinoma.…”
mentioning
confidence: 99%
“…In particular, it has been reported that Gleason pattern 5 can be under diagnosed on prostate needle core biopsy. 5 In summary, accurate histopathological diagnostic recognition of the many faces of high grade Glea- …”
mentioning
confidence: 99%